National and subnational burden of stroke in Iran from 1990 to 2019. Issue 5 (8th April 2022) - Fallahzadeh, Aida; Esfahani, Zahra; Sheikhy, Ali; Keykhaei, Mohammad; Moghaddam, Sahar Saeedi; Tehrani, Yeganeh Sharifnejad; Rezaei, Negar; Ghasemi, Erfan; Azadnajafabad, Sina; Mohammadi, Esmaeil; Koolaji, Sogol; Shahin, Sarvenaz; et al.
Abstract: Background: Data on the burden of stroke and changing trends at national and subnational levels are necessary for policymakers to allocate recourses appropriately. This study presents estimates of the stroke burden from 1990 to 2019 using the results of the Global Burden of Disease (GBD) 2019 study. Methods: For the GBD 2019, verbal autopsy and vital registration data were used to estimate stroke mortality. Cause‐specific mortality served as the basis for estimating incidence, prevalence, and disability‐adjusted life years (DALYs). The burden attributable to stroke risk factors was calculated by a comparative risk assessment. Decomposition analysis was applied to determine the contribution of population aging, population growth, and changes in the age‐specific incidence rates. Results: In 2019, the number of prevalent cases, incident cases, and deaths due to stroke in Iran were 963, 512; 102, 778; and 40, 912, respectively. The age‐standardized incidence rate (ASIR) and the age‐standardized death rate (ASDR) decreased from 1990 to 2019. Of national stroke ASDRs in 2019, 44.7% (35.7–54.7%) were attributable to hypertension and 28.8% (15.2–57.4) to high fasting plasma glucose. At the subnational level, the trend of the stroke incidence and mortality rate decreased in all provinces. Stroke was responsible for 4.48% of total DALYs in 2019 (3.38% due to ischemic stroke, 0.87% due to intracerebral hemorrhage, and 0.22% due to subarachnoid hemorrhage). Conclusion: ASIR and ASDR of stroke are decreasing nationally and subnationally; however, the number of incident cases and deaths are increasing in all SDI quintiles, possibly due to population growth.